DAHAGA: An Islamic spiritual mindfulness-based application to reduce depression among nursing students during the COVID-19 pandemic - Dwidiyanti, Meidiana; Munif, Badrul; Santoso, Agus; Rahmawati, Ashri Maulida; Prasetya, Rikhan Luhur (Belitung Raya Foundation, Indonesia, 2021)
Background: The COVID-19 pandemic significantly impacts students’ mental health. Most of them may experience depression. Due to restrictions and social distancing during the pandemic, counseling may not be applicable in detecting the problems. Therefore, an Islamic spiritual mindfulness-based application called DAHAGA is created in order to detect and reduce depression. It is believed that this innovative app could reduce mental health problems among students. Objective: This study aimed to determine the effect of DAHAGA on reducing depression among nursing students during the COVID-19 pandemic in Indonesia. Methods: This was a quasi-experimental study with a comparison group pretest/posttest design conducted from May to June 2020. Seventy students were selected using convenience sampling, of which 35 were assigned in an experimental group and a comparison group. The validated Indonesian Version-Beck Depression Inventory-II (BDI-II) was used for data collection. Paired t-test and independent t-test were used for data analysis. Results: There was a significant effect of DAHAGA on depression (p < 0.001). The level of depression after intervention (mean 11.49, SD 4.49) was lower than it before the intervention (mean 17.20, SD 4.94). Additionally, there was a significant difference in depression level between the experimental and comparison groups after the intervention with a p-value of < 0.001. Conclusion: The DAHAGA is proven effective in reducing depression. Therefore, this study offers a new and innovative app that fits with the COVID-19 pandemic to help Muslim students maintain their health status. The findings also support Islamic spiritual mindfulness as a part of nursing interventions among psychiatric nurses to deal with mental health problems, especially depression.